SMARCB1 (INI1)–Deficient Sinonasal Carcinoma With Yolk Sac Tumor Differentiation: Case Report and Review of the Literature. Issue 4 (July 2021) - Gradecki, Sarah E.; Kelting, Sarah M.; Stelow, Edward B.
Abstract : Abstract: SMARCB1 (INI1)–deficient sinonasal carcinoma is a recently described primary neoplasm of the sinonasal tract that occurs infrequently and displays aggressive clinical behavior. Classic histopathologic findings of INI1-deficient sinonasal carcinoma include sheets and nests of basaloid tumors cells with a monomorphic appearance. Variable amounts of rhabdoid and glandular differentiation have been reported. Diagnosis of this lesion can be challenging because of significant morphologic and immunohistochemical overlap between other primary lesions of the sinonasal tract, including basaloid and other nonkeratinizing squamous cell carcinomas, sinonasal undifferentiated carcinoma, and the newly described BRG1-deficient sinonasal carcinoma, among others. Recently, yolk sac tumor (YST)–like differentiation has been described in multiple reports of INI1-deficient sinonasal carcinoma, which expands both the histologic spectrum of this lesion and its differential diagnosis. Although there is significant immunophenotypic overlap between primary YST and INI1-deficient sinonasal carcinoma with YST differentiation, loss of INI1 expression by immunohistochemistry is not seen in YST. INI1 immunohistochemistry is a sensitive and specific marker for identifying INI1-deficient sinonasal carcinoma, and pathologists should have a low threshold for performing this test on tumors with a myriad of histologic features.